Attribution of physical complaints to the air disaster in Amsterdam by exposed rescue workers: an epidemiological study using historic cohorts - Huizink Anja C; Twisk Jos WR; Smidt Nynke; Slottje Pauline; Witteveen Anke B; van Mechelen Willem; Smid Tjabe (BMC, 2006)
Abstract Background In 1992 a cargo aircraft crashed into a residential area of Amsterdam. A troublesome aftermath followed, with rumors on potential toxic exposures and health consequences. Health concerns remained even though no excess morbidity was predicted in retrospective risk evaluations. This study aimed to assess to what extent the rescue workers attribute long-term physical complaints to this disaster, including its aftermath, and to examine associations between such attribution and types of exposure and background variables. Methods Historic cohort study that collected questionnaire data on occupational disaster exposure, attribution of physical complaints, and background variables on average 8.5 years post-disaster. For the present study the workers who were exposed to the disaster were selected from the historic cohort, i.e. the professional firefighters (n = 334), police officers (n = 834), and accident and wreckage investigators (n = 241) who performed disaster-related tasks. Results Across the three occupational groups, a consistent percentage (ranging from 43% to 49%) of exposed workers with long-term physical complaints attributed these to the disaster, including its aftermath. Those with more physical complaints attributed these to a stronger degree. Multivariate logistic regression analyses showed that attribution was significantly more often reported by firefighters who rescued people, and by police officers who reported the identification and recovery of or search for victims and human remains, clean-up, or security and surveillance of the disaster area; who witnessed the immediate disaster scene; who had a close one affected by the disaster; and who perceived the disaster as the worst thing that ever happened to them. Age, sex and educational level were not significantly associated with attribution. Conclusion This study provides further cross-sectional evidence for the role of causal attribution in post-disaster subjective physical health problems. After on average 8.5 years, almost a third (32%) of all the exposed workers, and almost half (45%) of the exposed workers with physical complaints, attributed these complaints to the disaster, including its aftermath. The similarity of the results across the occupational groups suggests a general rather than an occupation-specific attribution process. Longitudinal studies are needed to determine whether causal disaster attribution leads to persistence of post-disaster complaints and health care utilization.